The role of trauma and partner support in perinatal depression and parenting stress: An Australian pregnancy cohort study. (May 2019) - Galbally, Megan; Watson, Stuart J; Boyce, Philip; Lewis, Andrew J
Background: Improving our understanding of the relationship between maternal depression and parenting stress is likely to lie in the range of additional factors that are associated with vulnerability to depression and also to parenting stress. Objectives: To examine the role of trauma and partner support, in understanding the relationship between perinatal depression and parenting stress. Methods: This study utilises data from 246 women in a pregnancy cohort study that followed women from early pregnancy until their infant was 12 months. Included were both women with a diagnosis of depression and those without depression. The measures included Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Edinburgh Postnatal Depression Scale, Childhood Trauma Questionnaire, Social Support Effectiveness Questionnaire and the Parenting Stress Index. Results: We found women with depression were more likely to report a history of childhood trauma. Depressive symptoms were positively associated with parenting stress while partner support was negatively associated with parenting stress. The protective role of partner support for parenting distress was observed in those with no history of childhood abuse and low depressive symptoms, but not in those with a trauma history and high depressive symptoms. Conclusions: These findings highlight the importance of early trauma in understanding the protective role of support on the relationship between parenting and depression. These findings can inform future studies and the refinement of future interventions aimed at both perinatal depression and parenting.